Corrosion and tribocorrosion behaviour of Ti6Al4V produced by selective laser melting and hot pressing in comparison with the commercial alloy - Toptan, Fatih [UNESP]; Alves, Alexandra C.; Carvalho, Óscar; Bartolomeu, Flávio; Pinto, Ana M.P.; Silva, Filipe; Miranda, Georgina (Elsevier, 2019)
The corrosion and tribocorrosion behaviour of SLM-produced Ti6Al4V alloy was studied in comparison with its HP and commercial counterparts in 9 g/L NaCl solution at body temperature. Results showed that SLM processing route influenced the electrochemical response of the SLM-produced alloy by leading to a relatively lower quality for the passive film due to decreased β phase and the formation of α′ phase. However, after tribocorrosion, neither the total volume loss nor the volume loss under the influence of mechanical wear and wear-accelerated corrosion showed any statistically significant difference between the processing routes.
Keywords: Corrosion; hot pressing; selective laser melting; Ti6Al4V; tribocorrosion